2017
DOI: 10.1108/ecam-06-2016-0139
|View full text |Cite
|
Sign up to set email alerts
|

Building information modelling for facility management: are we there yet?

Abstract: Purpose Building information modelling (BIM) is increasingly being adopted during construction projects. Design and construction practices are adjusting to the new system. BIM is intended to support the entire project life-cycle: the design and construction phases, and also facility management (FM). However, BIM-enabled FM remains in its infancy and has not yet reached its full potential. The purpose of this paper is to identify major aspects of BIM in order to derive a fully BIM-enabled FM process. Design/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 127 publications
2
101
0
8
Order By: Relevance
“…These requirements are a part of the "Asset Information Requirements" document. This document is ideally provided by the facility management team and must contain a list of all the manageable assets in the building, as well as the required attributes for each asset that the construction supply chain will provide throughout building lifecycle (Edirisinghe et al, 2017). This change mandates a complete re-engineering of the traditional process of data preparation and exchange between construction and facilities management teams using COBie standard.…”
Section: Facilities Management Data and Bimmentioning
confidence: 99%
“…These requirements are a part of the "Asset Information Requirements" document. This document is ideally provided by the facility management team and must contain a list of all the manageable assets in the building, as well as the required attributes for each asset that the construction supply chain will provide throughout building lifecycle (Edirisinghe et al, 2017). This change mandates a complete re-engineering of the traditional process of data preparation and exchange between construction and facilities management teams using COBie standard.…”
Section: Facilities Management Data and Bimmentioning
confidence: 99%
“…Recent reviews of BIM implementation and research approaches in FM either covered digitisation in FM, where BIM was presented among other technologies [8,9]; or BIM implementation in FM, where the reviews analysed the existing research on BIM for FM and established trends [10]. Some of the reviews concentrate on specific aspects of BIM implementation in FM such as: BIM for FM with specific focus on refurbishment and maintenance [11]; energy retrofitting [12], knowledge management [13,14]; existing buildings [15], and as-is BIM model surveys [16]; Burno et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is hoped that this paper will advocate further developing a seamless information exchange process between BIM and FM systems to overcome interoperability issues and facilitate BIM implementation in FM.between facility's lifecycle stages, using an interoperable data format, data exchange and interoperability between BIM and FM systems still remain problematic. This paper aims to provide a comprehensive discussion concerning recent advances in the field of information exchange and interoperability between BIM and FM systems.Recent reviews of BIM implementation and research approaches in FM either covered digitisation in FM, where BIM was presented among other technologies [8,9]; or BIM implementation in FM, where the reviews analysed the existing research on BIM for FM and established trends [10]. Some of the reviews concentrate on specific aspects of BIM implementation in FM such as: BIM for FM with specific focus on refurbishment and maintenance [11]; energy retrofitting [12], knowledge management [13,14]; existing buildings [15], and as-is BIM model surveys [16]; Burno et al, 2018).…”
mentioning
confidence: 99%
“…Despite numerous benefits reported, past research [27] [28] [29] found BIM applications in FM still at the initial and emerging stages and encouraged further research to address the existing implementation challenges. Challenges found in these research efforts for incorporation of BIM in FM can be summarized as: absence of structured method for incorporating BIM in FM processes; lack of proper tools for demonstrating BIM benefits to FM; limited knowledge on types of information to be collected and methods and tools to be used for applying BIM in FM; too much detailed specifications required for BIM development; lack of expertise for working with BIM in public organizations; resistance to change previously adopted methods; and challenges for linking BIM to the current tools used in FM.…”
Section: -Use Of Bim In Fm Processesmentioning
confidence: 99%
“…Maintenance operations applied to various hospital facilities identified in the 3D models could be recorded in the existing CMMS using the same identification numbers. Nevertheless, gradually integration level of FM processes with the BIM models could be increased as BIM maturity level of the organization increases [29].…”
Section: -Implementation Architecturementioning
confidence: 99%